2017
DOI: 10.2147/ott.s135514
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential biomarkers and analysis of prognostic values in head and neck squamous cell carcinoma by bioinformatics analysis

Abstract: The purpose of this study was to find disease-associated genes and potential mechanisms in head and neck squamous cell carcinoma (HNSCC) with deoxyribonucleic acid microarrays. The gene expression profiles of GSE6791 were downloaded from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) were obtained with packages in R language and STRING constructed protein–protein interaction (PPI) network of the DEGs with combined score >0.8. Subsequently, module analysis of the PPI network was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“… 30 We found that the turquoise module played a role in the BPs and pathways, mainly in the regulation of ECM and collagen catabolic process, which play important roles in malignancy. 31 The results were in accordance with previous reports 32 that analyzed the DEGs between normal samples and OSCC in which the function of ECM was stressed and the MMP family and laminin family play an important role in tumorigenesis of OSCC. 33 These findings revealed the function of the turquoise module in OSCC, and further research is required to identify the role of the genes in the turquoise module because they might have diverse functions in OSCC malignant phenotypes.…”
Section: Discussionsupporting
confidence: 90%
“… 30 We found that the turquoise module played a role in the BPs and pathways, mainly in the regulation of ECM and collagen catabolic process, which play important roles in malignancy. 31 The results were in accordance with previous reports 32 that analyzed the DEGs between normal samples and OSCC in which the function of ECM was stressed and the MMP family and laminin family play an important role in tumorigenesis of OSCC. 33 These findings revealed the function of the turquoise module in OSCC, and further research is required to identify the role of the genes in the turquoise module because they might have diverse functions in OSCC malignant phenotypes.…”
Section: Discussionsupporting
confidence: 90%
“…Potential biomarkers with high specificity and sensitivity, identified in datasets by distinct Bioinformatic methods, have been continuously explored (Sun et al, 2015). Previous studies have determined a number of target genes by filtering DEGs in datasets (Yang et al, 2017;Zhao et al, 2018). Still, given the differences in specimens and database platforms, potential markers have failed to bear a significant clinical application value, so their verification process have been far from clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) ranks the sixth most prevalent cancer and comprises 5% of worldwide malignancies. 1,2 It is pathogenically heterogeneous and happens within oral cavity, larynx or pharynx. 3,4 People engaged in alcohol consumption, smoking or poor oral hygiene are under high risk of HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…4 About 650,000 new cases and 350,000 deaths are reported annually, with its increasing incidence. 1,4 Poor prognosis of HNSCC is evidenced by that 5-y survival is about 50%, owing to likelihood of recurrence, metastasis or therapeutic resistance. 1 Despite the discovery of a number of biomarkers, the molecular mechanisms underlying the pathogenesis of HNSCC remains elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation